Functional Aspects of Verbs in Scientific Writing - Shekhar, Shashank; Achintya (JOURNAL OF INDIAN EDUCATION, 2021)
The study highlights the semantic variations of verbs used in scientific writing. Although, there is no rigid rule in grammar regarding the use of semantically varying verbs in written technical communication; however, the behavioural pattern of verbs, with their effective usage, may add to the purpose for which they have been used. A particular verb, if used in another similar context, may distort the exact meaning. An array of examples has been drawn to drive home the fact. Further, it has also been taken into consideration the use of infinitive, gerund, prefixes and dental prefixes as necessary accompaniments of verbs used in science. One of the cardinal features of scientific writing is the exhaustive use of phrasal verbs. Use of verbs with prepositions added to them acquires new meaning and expands and enriches the frontiers of technical writing. The user however, needs to develop familiarity with such usages which are often used in scientific and technical writing.